Clinical Utility of Deutetrabenazine as a Treatment Option for Chorea Associated with Huntington’s Disease and Tardive Dyskinesia - Frank S; Alakkas A (Dove Medical Press, 2023)
Samuel Frank,1 Aljoharah Alakkas2 1Department of Neurology, Beth Israel Deaconess Medical Center/Harvard Medical School, Boston, MA, USA; 2Department of Neurology, National Neuroscience Institute, King Fahad Medical City, Riyadh, K.S.ACorrespondence: Samuel Frank, Department of Neurology, Beth Israel Deaconess Medical Center/Harvard Medical School, 330 Brookline Ave, Kirstein 228, Boston, MA, 02215, USA, Tel +1 617-667-4889, Fax +1 617-975-5454, Email sfrank2@bidmc.harvard.eduAbstract: Deutetrabenazine (DTBZ) is used for the treatment of tardive dyskinesia (TD) and chorea in Huntington's Disease (HD). Four pivotal clinical trials showed the efficacy of DTBZ in these conditions. Long term follow-up studies confirmed evidence of overall safety and continued efficacy of this drug. Indirect comparisons revealed relative superiority of DTBZ over TBZ in terms of safety, but direct comparisons of safety and efficacy between the VMAT2 and dopamine blocking agents is lacking. Deutetrabenazine is safe and effective in the treatment of TD and chorea in HD in doses up to 72 mg daily and for up to three years in duration.Keywords: chorea, tardive dyskinesia, hyperkinetic movement disorders, VMAT2 inhibitors